Security of property as a public good: Institutions, socio-political environment and experimental behavior in five countries - Francisco Campos-Ortiz; Louis Putterman; T. K. Ahn; Loukas Balafoutas; Mongoljin Batsaikhan; Matthias Sutter (Brown University, Department of Economics, 2012)
We study experimentally the protection of property in five widely distinct countries - Austria, Mexico, Mongolia, South Korea and the United States. Our main results are that the security of property varies with experimental institutions, and that our subject pools exhibit significantly different behaviors that correlate with country-level property security, trust and quality of government. Subjects from countries with higher levels of trust or perceptions of safety are more prone to abstain initially from theft and devote more resources to production, and subjects from countries with higher quality political institutions are more supportive of protecting property through compulsory taxation. This highlights the relevance of socio-political factors in determining countries' success in addressing collective action problems including safeguarding property rights.
Keywords: C91; C92; D03; H41; P14; 330; Property Rights; Theft; Efficiency; Experiment; Socio-Political Factors; Eigentumsrecht; Experimentelle Ökonomik; Verhaltensökonomik; Öffentliche Güter; Österreich; Mexiko; Mongolei; Südkorea; USA